Therapeutic patellar taping changes the timing of vasti muscle activation in people with patellofemoral pain syndrome - Cowan, S. M.; Bennell, K. L.; Hodges, P. W. (Clinical Journal of Sport Medicine, 2002)
Objective: To examine the effect of the application of tape over the patella on the onset of electromyographic (EMG) activity of vastus medialis obliquus (VMO) relative to vastus lateralis (VL) in participants with and without patellofemoral pain syndrome (PFPS). Design: Randomised within subject. Settings: University laboratory. Participants: Ten participants with PFPS and 12 asymptomatic controls. Interventions: Three experimental taping conditions: no tape, therapeutic tape, and placebo tape. Main Outcome Measures: Electromyographic onset of VMO and VL assessed during the concentric and eccentric phases of a stair stepping task. Results: When participants with PFPS completed the stair stepping task, the application of therapeutic patellar tape was found to alter the temporal characteristics of VMO and VL activation, whereas placebo tape had no effect. In contrast, there was no change in the EMG onset of VMO and VL with the application of placebo or therapeutic tape to the knee in the asymptomatic participants. Conclusions: These data support the use of patellar taping as an adjunct to rehabilitation in people with PFPS.